Pengembangan Media Animasi Pada Pembelajaran Elektronika Siswa SMK - Yusnidah, Yusnidah (Universitas Negeri Malang, 2022)
The purpose of this development research is to describe the process of developing electronic learning animation media for SMK students, describe the validation of animation media development from material experts and electronic learning media experts of SMK students, describe the feasibility of electronic learning animation media for SMK students. The data used is descriptive qualitative which is the main data through instruments from material expert respondents and media experts. The research used the Borg and Gall models which were adjusted based on 6 stages due to the situation and conditions of the Covid-19 pandemic, namely needs analysis, product specification planning, product design, product validation, product revision, and dissemination. The use of Canva Pro was used in the animation media development process with the response of material experts obtained an overall average of 79.17%, the category of